PHYSICAL EXERCISE AFTER IMMOBILIZATION OF SKELETAL MUSCLE OF ADULT AND AGED RATS - Koike, Tatiana Emy [UNESP]; Watanabe, Adriana Yukie [UNESP]; Kodama, Fabio Yoshikazu [UNESP]; Tamura Ozaki, Guilherme Akio; Castoldi, Robson Chacon; Garcia, Thiago Alves [UNESP]; Trindade Camargo, Regina Celi [UNESP]; Silva Camargo Filho, Jose Carlos [UNESP] (Soc Brasileira Med Esporte, 2018)
Introduction: Immobilization is a treatment technique often used to reduce pain and prevent worsening of the injury. However, it promotes harmful effects on musculoskeletal tissue, resulting in a marked loss of muscle function, which may be aggravated in the elderly. Physical exercise is an important intervention to mitigate these harmful effects. Objective: To analyze possible morphometric changes in the gastrocnemius muscle of rats after immobilization and remobilization with physical exercise. Methods: Fifty-six rats were divided into adult (A) and aged (E) groups and subdivided into adult and aged control (AC and EC), immobilized (AI and EI), free remobilized (AIF and EIF), and remobilized through physical exercise (AIE and EIE). The hind limbs were immobilized with the gastrocnemius muscle in a shortened position for a period of seven days, except for the control group. The exercise protocol consisted of five swimming sessions, once per day (25 minutes/session). The animals were euthanized by administration of an overdose of ketamine hydrochloride plus xylazine hydrochloride, followed by sample collection and preparation of hematoxylin and eosin slides. Measurements of the smallest diameter of 120 muscle fibers of each animal were taken with software NIS-Elements D3.0-SP7-Nikon (R) instruments Inc., NY, USA. Results: There was a significant reduction in the mean fiber diameter in the AI (38.43 mu m +/- 4.20; p= 0.01) and AIF (36.97 mu m +/- 3.41; p< 0.01) groups compared to AC (45.39 mu m +/- 3.41) and in the EI (42.26 mu m +/- 4.39; p< 0.01), EIF (36.00 mu m +/- 4.15; p< 0.01), and EIE (41.86 mu m +/- 4.95; p< 0.01) groups compared to the EC (51.37 mu m +/- 3.86) group. The data showed that exercise was able to restore muscle trophism in the adult groups; however, none of the protocols has succeeded in aged rats. Conclusion: Immobilization in the shortened position induced muscle atrophy and physical exercise was effective in restoring muscular trophism only in adult animals. Level of Evidence I; Therapeutic studies Investigating the Results of Treatment.
Keywords: Muscle; skeletal; Immobilization; Physical exercise; Age factors